Incidence of Non-Communicable Diseases and Out-of-Pocket Expenditure among Senior Elderly of five Districts in Kerala - N, Parvathy; Divi, Sriram; Dorasamy, Nirmala (South Eastern European Journal of Public Health, 2024)
Background: The nation's healthcare system, which is already struggling with constraints, faces a significant challenge from India's growing elderly population. As the prevalence of non-communicable diseases (NCDs) rises among this demographic, concerns mount over the strain on healthcare services. Objective: the study's primary aim was to evaluate the incidence of NCDs and the financial burden of out-of-pocket expenses associated with hospital stays for the middle-aged and older segments of the population. Methods: The referenced study, employing a systematic random sampling method, sought to gather pertinent data within Kerala—a state in southern India. Conducted across five specific districts. Results: The findings from a sample of 500 individuals revealed that 45% were afflicted with NCDs. Notably, a significant majority of these patients, irrespective of their economic status, opted for private healthcare providers, accounting for 60.5% of the respondents. This preference underscores the perceived or actual disparities in the quality of care between private and public healthcare institutions. Conclusions: The study's insights are crucial in understanding the healthcare dynamics at play and could serve as a catalyst for policy reform, aiming to enhance the accessibility and affordability of healthcare for India's aging population. It also highlights the urgent need for a robust healthcare system that can accommodate the complex needs of the elderly, particularly in managing chronic conditions that require long-term care and substantial financial resources. Way ahead: Utilising frontline staff (ANMs and ASHAs) can assist in putting NCD interventions into practice at the community level.